INFLUENCE OF DISTRIBUTION NETWORK SYSTEMS ON SUPPLY CHAIN PERFORMANCE IN PRINT MEDIA INDUSTRY IN KENYA: A CASE OF THE NATION MEDIA GROUP - Kiriba, Teresiah Wanjiru; Ishmail, Dr. Noor (International Journal of Supply Chain Management, 2017)
Purpose: The global publishing industry is going through difficulty times as a broadband penetration rises and new devices for delivering news and content arrive on the scene. Distribution in the printing industry addresses not only outbound distribution but also inbound distribution. This study sought to assess the extent to which warehousing influences supply chain performance in media industry, to determine the influence of Transportation on supply chain performance in media industry, to find out how technology affect supply chain performance in media industry and to determine the influence of distribution channels on supply chain performance in media industry. The study was carried out at Nation Media Limited in Nairobi County. Methodology: The study adopted a descriptive research design. The total population of the study was all the employees working at Nation Media Group, print media section. The study sampled 222 respondents who participated in the study. The research used the simple random sampling method because it gave every member of the population equal chances of being selected. Structure questionnaire were used to collect the primary data from the sample size. The raw data from the respondent was analyzed using statistical package for social science (SPSS) analysis software and findings presented using descriptive statistical tools like graphs and tables. Results: The study established a positive relationship between the independent variables and the dependent variable. Transportation was identified as very critical component of ensuring that the overall costs of operations are significantly reduced. The study indicated that the organizations need to put in place the cost control measures which will eventually result to cost reduction in the entire supply chain. The study established a positive relationship between warehousing and supply chain performance in Print media industry in Kenya. The location of warehouses in places accessible by all partners in the chain of distribution is very important in ensuring on time delivery of the product to ultimate consumers. The study has established a positive relationship between the application of information technology and supply chain performance in Print media industry in Kenya. Application of information technology has been identified as a very critical aspect that facilitates reduction of operation costs, on time delivery and customer satisfaction along the supply chain. Conclusion and policy recommendation: The study concluded that efficient distribution network system has the capability of enhancing, products quality, delivery time, customer satisfactions and reduced lead time in the supply chain.